2016
DOI: 10.1111/desc.12445
|View full text |Cite
|
Sign up to set email alerts
|

Implicit and explicit false belief development in preschool children

Abstract: The ability to represent the mental states of other agents is referred to as Theory of Mind (ToM). A developmental breakthrough in ToM consists of understanding that others can have false beliefs about the world. Recently, infants younger than 2 years of age have been shown to pass novel implicit false belief tasks. However, the processes underlying these tasks and their relation to later-developing explicit false belief understanding, as well as to other cognitive abilities, are not yet understood. Here, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
125
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(144 citation statements)
references
References 48 publications
15
125
1
Order By: Relevance
“…This is in line with a large body of evidence on the close link between both cognitive domains (for a recent meta-analysis, see Devine and Hughes, 2014). Further, consistent with recent evidence (Low, 2010; Grosse Wiesmann et al, 2016), we found that executive function task performance was related to performance in the explicit, but not in the implicit mentalizing task. This provides further support for two-systems accounts of mentalizing (Apperly and Butterfill, 2009; cf., Perner and Roessler, 2012).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is in line with a large body of evidence on the close link between both cognitive domains (for a recent meta-analysis, see Devine and Hughes, 2014). Further, consistent with recent evidence (Low, 2010; Grosse Wiesmann et al, 2016), we found that executive function task performance was related to performance in the explicit, but not in the implicit mentalizing task. This provides further support for two-systems accounts of mentalizing (Apperly and Butterfill, 2009; cf., Perner and Roessler, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Yet, this remains to be proven empirically. Together with other recent work (Low, 2010; Senju et al, 2010; Grosse Wiesmann et al, 2016), our findings suggest that implicit mentalizing indeed is a phenomenon presumably persisting across lifespan.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We therefore additionally assessed and controlled for a battery of executive function and language tests27 to understand to what extent the maturation of distinct brain structures uniquely supported the emergence of false belief understanding. Moreover, in the past decade, implicit false belief tasks have been developed which showed that, already before the age of 2 years, infants display correct expectations of the actions of an agent with a false belief in their looking behaviour2829.…”
mentioning
confidence: 99%
“…A second hint comes from correlational studies comparing children's performance in SR-and ERFBTs (Grosse Wiesmann et al 2016;Low 2010). These studies found no stable relation between children's (implicit) predictive looking in SR-FBTs and their (explicit) verbal response in ER-FBTs.…”
mentioning
confidence: 99%